Safer Tractor Operations for Florida's Privately Owned and Operated Farms and Ranches - Carol J. Lehtola; Charles M. Brown (EDIS)
This document is CIR 1250,one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published September 2002.